2000
DOI: 10.1046/j.1365-3083.2000.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fcγr1 (CD64) on Polymorphonuclear Leucocytes during Progression to Acquired Immunodeficiency Syndrome in Perinatally Human Immunodeficiency Virus‐Infected Children

Abstract: CD64, the high‐affinity receptor in the family of FCγ receptors, is not expressed constitutively in polymorphonuclear leucocytes (PMN). CD64 is expressed by PMNs in the late stages of human immunodeficiency virus (HIV) infection in adults. We followed the expression of CD64 on PMNs in perinatally HIV‐infected children during disease progression. Peripheral blood leucocytes (PBL) from 45 perinatally HIV‐infected paediatric patients and 13 healthy age‐matched controls were analysed using cytofluorimetry after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Fjaertoft and colleagues 9 reported increased neutrophil CD64 expression in patients with influenza A infection, especially in those with complications. Moallem and colleagues 19 found a significant increase in neutrophil CD64 expression as perinatally infected human immunodeficiency virusYinfected children progressed to acquired immunodeficiency syndrome. The increased CD64 expression observed in these 2 studies might be explained by a significant increase in interferon-+ production in these viral infections.…”
Section: Discussionmentioning
confidence: 98%
“…Fjaertoft and colleagues 9 reported increased neutrophil CD64 expression in patients with influenza A infection, especially in those with complications. Moallem and colleagues 19 found a significant increase in neutrophil CD64 expression as perinatally infected human immunodeficiency virusYinfected children progressed to acquired immunodeficiency syndrome. The increased CD64 expression observed in these 2 studies might be explained by a significant increase in interferon-+ production in these viral infections.…”
Section: Discussionmentioning
confidence: 98%
“…In these ART-treated HIV-infected adults, immune activation and persistent inflammation fuel non-AIDS-defining events such as cardiovascular disease and non-AIDS-defining malignancies. CD64 expression could be correlated to HIV stage disease in infants perinatally infected by HIV (25). Selective defects of neutrophil functions have been also reported with relation to HIV infection (23).…”
Section: Introductionmentioning
confidence: 86%
“…These impairments of innate response in HIV infected individuals may be involved in the increased susceptibility to bacterial infections observed despite immune reconstitution on ART (24). CD64 expression could be correlated to HIV stage disease in infants perinatally infected by HIV (25).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Other studies have reported a similar association between elevation in polymorphonuclear neutrophil CD64 expression and the presence of infection. [14][15][16][17][18][19][20][21][22][23] However, neutrophil CD64 expression is not used for diagnosis of AA yet.…”
Section: Introductionmentioning
confidence: 99%